Wzorzec płodności a wzorzec małżeńskości w Polsce po okresie transformacji - Podogrodzka, Małgorzata (Space – Society – Economy, 2013)
Observed since the beginning of the 1990s. changes in the intensity of marriages and fertility are the result of different of their raters by age. At the same time, these processes are different in urban and rural areas and by voivodeships. The purpose of the article is their description and shows how degree of the pattern of fertility determines the degree of pattern of marriages by voivodeships. We expect that the stronger changes of one of the process also means stronger the second changes. Carried out considerations have not confirmed this assumption.